2014
DOI: 10.1371/journal.pone.0107734
|View full text |Cite
|
Sign up to set email alerts
|

Protective Vascular and Cardiac Effects of Inducible Nitric Oxide Synthase in Mice with Hyperhomocysteinemia

Abstract: Diet-induced hyperhomocysteinemia produces endothelial and cardiac dysfunction and promotes thrombosis through a mechanism proposed to involve oxidative stress. Inducible nitric oxide synthase (iNOS) is upregulated in hyperhomocysteinemia and can generate superoxide. We therefore tested the hypothesis that iNOS mediates the adverse oxidative, vascular, thrombotic, and cardiac effects of hyperhomocysteinemia. Mice deficient in iNOS (Nos2−/−) and their wild-type (Nos2+/+) littermates were fed a high methionine/l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…Each of these genetic alterations results in hyperhomocysteinemia. Models using diets containing low folate and/or high methionine to induce hyperhomocysteinemia are also common (Table) (Dayal et al, 2014; Kamat et al, 2015; Kim et al, 2002). …”
Section: Hyperhomocysteinemiamentioning
confidence: 99%
“…Each of these genetic alterations results in hyperhomocysteinemia. Models using diets containing low folate and/or high methionine to induce hyperhomocysteinemia are also common (Table) (Dayal et al, 2014; Kamat et al, 2015; Kim et al, 2002). …”
Section: Hyperhomocysteinemiamentioning
confidence: 99%
“…In hyperhomocysteinemic rats, there is upregulation of iNOS in the carotid and the coronary artery (Ungvari et al, ; Zhang et al, ; Celotto et al, ) and iNOS inhibitors mitigate the increased ROS production in the carotid and the coronary artery (Dayal et al, ). However, Dayal et al () have shown that in diet induced hyperhomocysteinemic mice, endogenous iNOS protects from endothelial dysfunction and myocardial ischemia‐reperfusion injury. The present findings suggest that upregulation of iNOS, with increased production of superoxide radicals; underline the mechanism of vascular dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…However, Dayal et al (2014) have shown that in diet induced hyperhomocysteinemic mice, endogenous iNOS protects from endothelial dysfunction and myocardial ischemia-reperfusion injury. The present findings suggest that upregulation of iNOS, with increased production of superoxide radicals; underline the mechanism of vascular dysfunction.…”
Section: Journal Of Cellular Physiologymentioning
confidence: 99%
“…This is the first study to investigate the effects of perfusing normal isolated hearts with Hcy on cardiac functional parameters during ischaemia reperfusion. Previous studies of the effects of homocysteine during ischaemia reperfusion have either investigated transgenic mice [15], or have explored oxidant damage [16] or area at risk [17] in methionine fed animals. The results showed that exposure to 0.1mM Hcy prior to global normothermic ischaemia impaired recovery of LVDP (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Two studies have shown impaired functional recovery following ischaemia reperfusion in transgenic cystathionine beta synthase deficient mice and increased reperfusion damage [15] and oxidant damage in methionine fed rat hearts [16] and increased area at risk in methionine fed mice [17]. Therefore the aim of this study was to specifically investigate the effect of exposing whole hearts and isolated cardiomyocytes to the clinically relevant dose of 0.1 mM Hcy on functional performance during ischaemia reperfusion and on calcium homeostasis, morphology and viability, and contractile activity under normal conditions and during oxidative stress.…”
Section: Introductionmentioning
confidence: 99%